2015
DOI: 10.3109/09513590.2014.994598
|View full text |Cite
|
Sign up to set email alerts
|

Should insulin resistance be screened in lean hirsute women?

Abstract: The role of insulin resistance (IR) is well-documented in obese women with polycystic ovary syndrome (PCOS). Controversies exist concerning the presence of IR in idiopathic hirsutism (IH) or if it is a manifestation of high body mass index (BMI). We aimed to investigate the presence/absence of IR in lean hirsute women. One-hundred fifty-one lean women with hirsutism [96 PCOS (group 1) and 55 IH (group 2)] and 58 age-and BMI-matched healthy controls (group 3) were recruited in the study (mean age 25.21 ± 6.1 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…Our finding that total mFG scores were neither predictive of, or related to, total testosterone levels is supported by some (24, 29, 44, 46) but not all studies (9, 47, 48). Differences in findings might relate to the inclusion of more severe manifestations of hirsutism in women with overt androgen excess disorders by some studies (12, 13, 45) as well as differences in the racial and ethnic groups investigated (1215).…”
Section: Discussionsupporting
confidence: 40%
“…Our finding that total mFG scores were neither predictive of, or related to, total testosterone levels is supported by some (24, 29, 44, 46) but not all studies (9, 47, 48). Differences in findings might relate to the inclusion of more severe manifestations of hirsutism in women with overt androgen excess disorders by some studies (12, 13, 45) as well as differences in the racial and ethnic groups investigated (1215).…”
Section: Discussionsupporting
confidence: 40%
“…7 In addition to the negative consequences of IH on the psychological health and quality of life of women, 8,9 this disease can be associated with some metabolic disturbances, such as insulin resistance, elevated insulin, and glucose intolerance. 3,10 Epidemiologic studies indicate that hyperinsulinemia and insulin resistance are frequent in both patients with IH and PCOS, and are associated with an increased risk of glucose intolerance, dyslipidemia, and cardiovascular disease. 11,12 Earlier studies have been demonstrated a link between insulin resistance and hyperandrogenism, 13 even in non-obese women.…”
Section: Introductionmentioning
confidence: 99%
“…Obese women with PCOS are characterized by insulin resistance, which increases the risk of metabolic and cardiovascular diseases [ 15 ]. In obese patients with PCOS, insulin resistance is higher than in non-obese patients with PCOS [ 16 ], but even in non-obese patients, insulin resistance is higher than that of controls [ 17 , 18 ]. Insulin resistance is defined as a state of subnormal to abnormal glucose utilization and homeostasis under normal concentrations of insulin production, and PCOS with obesity commonly amplifies the degree of these metabolic abnormalities [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%